2019
DOI: 10.1002/fee.2060
|View full text |Cite
|
Sign up to set email alerts
|

Punching above their weight: the ecological and social benefits of pop‐up parks

Abstract: Current global enthusiasm for urban greening and bringing nature back into cities is unprecedented. Evidence of the socioecological benefits of large, permanent greenspaces is mounting, but the collective potential for pop‐up parks (PUPs) – small, temporary greenspaces – to augment urban ecosystem services is unknown. To showcase the potential of PUPs, we first highlight a case study demonstrating how PUPs may enhance biodiversity in a densely urbanized area; we then review evidence linking the design of small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Such efforts are already underway in many parts of the world. For example, the blue-banded bee (Amegilla cingulata) in Melbourne, Australia, is being actively supported using planted habitats, but the designers and managers are already considering how to construct and maintain metanetworks of bee subpopulations (Mata et al, 2019). Although their approach does not yet include additional trophic dynamics (e.g., introducing neon cuckoo bees or bird species that prey on blue-banded bees), this build-it-and-they-will-come approach recognizes that food webs are often anchored by a few key species.…”
Section: Ecological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such efforts are already underway in many parts of the world. For example, the blue-banded bee (Amegilla cingulata) in Melbourne, Australia, is being actively supported using planted habitats, but the designers and managers are already considering how to construct and maintain metanetworks of bee subpopulations (Mata et al, 2019). Although their approach does not yet include additional trophic dynamics (e.g., introducing neon cuckoo bees or bird species that prey on blue-banded bees), this build-it-and-they-will-come approach recognizes that food webs are often anchored by a few key species.…”
Section: Ecological Considerationsmentioning
confidence: 99%
“…Others have found that urban systems have considerable species diversity and support locally rare or endangered native species. For example, changes in productivity and habitat structures in cities may favor specific species of birds (Marzluff and Ewing, 2008), spiders (Shochat et al, 2008), bees (Mata et al, 2019), or amphibians (Hamer and McDonnell, 2008). This urban biodiversity increasingly is valued and deliberately cultivated in more intentionally designed urban green spaces (Aronson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, as argued by Singh et al (2018), establishment of urban nature reserves to create space for biodiversity to flourish and to promote wellbeing of city dwellers, needs to be made mandatory while planning a city. Although we acknowledge the central role of large, permanent green spaces, here we draw attention to the emerging opportunity presented by small-scale, short-lived green spaces such as pop-up parks (PUPs) to synergistically enrich urban nature for the benefit of biodiversity and people (Mata et al, 2019). PUPs may help people rekindle their connections with nature, socialize, spend time outdoors, and experience positive short-term body and mind states.…”
Section: Contribution To Biodiversitymentioning
confidence: 99%
“…A parallel, yet limited, body of applied research has focused on providing evidence of the positive benefits of BNB actions. For example, a recent study assessing the insect and spider community of a pop‐up park that brought a native grassland back into central Melbourne for 6 weeks found that the temporary vegetation sustained almost twice as many native insect species as the site's pre‐existing vegetation (Mata et al, 2019). Despite these theoretical and empirical advances, much work is needed to tackle the complexities involved in translating BNB research into practice (McDonnell & Hahs, 2013; Ossola & Niemelä, 2017).…”
Section: Introductionmentioning
confidence: 99%